2022
DOI: 10.1039/d2bm00319h
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic bioactive glass nano-heterostructures: a deeper insight into magnetic hyperthermia properties in the scope of bone cancer treatment

Abstract: Primary bone cancers commonly involve surgery to remove the malignant tumor, complemented with a postoperative treatment to prevent cancer resurgence. Studies on magnetic hyperthermia, used as a single treatment or...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Moreover, the addition of Cu to the Fe-doped BGs enhanced their bioactivity, cytocompatibility, and antibacterial activity which is a critical parameter in tissue engineering approaches. Magnetic nanocomposites made of BGs and iron oxides have been previously reported as suitable compositions in magnetic hyperthermia and bone cancer treatment (Vergnaud et al, 2022). Recently, Borges et al fabricated superparamagnetic and highly bioactive nanocomposites by adding 10-30 wt% SPIONs to the sol-gel derived 58S BG (58SiO 2 -33CaO-9P 2 O 5 , wt%) and investigated their potential in magnetic hyperthermia (Borges, Ferreira, et al, 2022).…”
Section: Nbgs For Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the addition of Cu to the Fe-doped BGs enhanced their bioactivity, cytocompatibility, and antibacterial activity which is a critical parameter in tissue engineering approaches. Magnetic nanocomposites made of BGs and iron oxides have been previously reported as suitable compositions in magnetic hyperthermia and bone cancer treatment (Vergnaud et al, 2022). Recently, Borges et al fabricated superparamagnetic and highly bioactive nanocomposites by adding 10-30 wt% SPIONs to the sol-gel derived 58S BG (58SiO 2 -33CaO-9P 2 O 5 , wt%) and investigated their potential in magnetic hyperthermia (Borges, Ferreira, et al, 2022).…”
Section: Nbgs For Hyperthermiamentioning
confidence: 99%
“…For example, the potential effects of the size and shape of magnetic NBGs on their heat generation capacity are of utmost importance in this area of science. In addition, the combination method of SPIONs to BGs can affect the superparamagnetic properties of final products (Kesse et al, 2020; Vergnaud et al, 2022); for example, SPIONs embedded into/deposited onto the glasses has led to generating NBGs with different particle size and superparamagnetic features (Taşar & Ercan, 2023). Since physicochemical parameters (e.g., size and shape) of SPIONs can influence their magnetic properties (Choi et al, 2013; Kandasamy & Maity, 2015; Wortmann et al, 2014), BGs containing SPIONs may exhibit vary superparamagnetic characteristics in vitro and in vivo.…”
Section: Nbgs For Cancer Therapymentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org regulate bone metabolism in vitro and in vivo, and that they have favorable bone targeting, bone regeneration and biocompatibility properties. For instance, Zheng et al (2022) revealed that IONPs can alleviate osteoporosis induced by ovariectomized mice (OVX) by scavenging reactive oxygen species, promoting osteogenic differentiation of BMSCs and inhibiting osteoclastogenesis in vitro. Krzysztof et al (Marycz et al, 2022) combined aminopropyltriethoxysilane (APTES) modified nHAp with IO nanoparticles and demonstrated in vitro that this biomaterial promotes osteoblast viability and RUNX-2 expression, reduces osteoclast metabolism and inflammation, and can be used for healing of osteoporotic fractures.…”
Section: Figure 12mentioning
confidence: 99%
“… Sasikala et al (2022) developed a piezoelectric magnetic nanoparticle (PMNP) that can regulate cell behaviour and fate under ultrasound (US), magnetic field (MF) and light-responsive conditions to achieve superior bone regeneration and bone transformation after bone tumour surgery. Vergnaud et al (2022) designed superparamagnetic bioactive nanoparticles with an IO core (γ-Fe2O3) wrapped in a bioactive glass (SiO2-CaO) shell, which demonstrated in vitro experiments its non-toxic, bone healing and thermal therapeutic properties for direct or combined scaffolding of bone defects after bone tumour resection. It is apparent that IONPs have a great platform and opportunity in the treatment of pathological bone defects and have now gained great traction.…”
Section: Application Of Iron Oxide Nanoparticles In Pathological Bone...mentioning
confidence: 99%